(untitled) (Latakia University (formerly Tishreen) Journal for Research and Scientific Studies - Arts Humanities Series, 2026)
In the poem "The Strange Nightingale" by Badawi al-Jabal, a complex semantic structure emerges that transcends direct lexical observation toward emotional reality. Semantic fields intertwine to form a cosmic vision where the self merges with homeland and humanity. The field of suffering and pain dominates the text as a regulating emotional nucleus. The text moves from the burning ego to childhood, embodied in the grandson Muhammad. The semantic fields of place, values, and religion operate through contrast; the parallelism between the child’s physiological movements—cooing and crawling—and the value of Eid elevates the mundane to the sacred. The evocation of Syrian geography is not topographical description, but a summoning of identity in the face of alienation. The nightingale’s symbolism transforms the experience from a personal cry into a cosmic song transcending places, balancing loss’s melancholy with creation’s joy. Badawi al-Jabal’s semantic fields are not mere lexical classification, but tools of cognitive excavation that turn personal pain into existential philosophy, and exile into spiritual transcendence. The word does not remain confined to its static lexical denotation; rather, it generates worlds of suggestive connotations that reshape reality according to the creator’s vision.